2010
DOI: 10.1515/cclm.2011.062
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cigarette smoking on plasma homocysteine concentrations

Abstract: Cigarette smoking increases homocysteine, which is strongly correlated with cotininuria and plasma thiocyanates. Moreover, smokers had tendency to develop hypofolatemia and hypovitamin B12, particularly when the duration of consumption exceeded 20 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
30
4
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 12 publications
4
30
4
1
Order By: Relevance
“…Cigarette smoking has been reported to be associated with increased levels of plasma homocysteine and decreased levels of serum folate and vitamin B12 [25]. However, cigarette smoking had no significant effect on mean concentrations of plasma homocysteine, serum folate, vitamin B12, PLP and blood Pb in males in the present study.…”
Section: Discussioncontrasting
confidence: 73%
“…Cigarette smoking has been reported to be associated with increased levels of plasma homocysteine and decreased levels of serum folate and vitamin B12 [25]. However, cigarette smoking had no significant effect on mean concentrations of plasma homocysteine, serum folate, vitamin B12, PLP and blood Pb in males in the present study.…”
Section: Discussioncontrasting
confidence: 73%
“…Various lifestyle factors, such as smoking, have been associated with an increased level of tHcy [10,11] and, thus, identification of such factors could help to prevent diseases related to hyperhomocysteinemia. In our study, an impressive high proportion of smoking pregnant women was found (25.6%).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, although smokers showed a higher average folate intake, their mean RBC folate level was lower than in nonsmokers, and, among smokers, a higher proportion had RBC folate levels below the recommended reference value. Some authors [11,28] propose a number of mechanisms that may cause this deficiency, including the interaction of some components of tobacco smoke with folic acid coenzymes, which transforms them into biologically inactive compounds that lead to decreased circulating folic acid concentrations in smokers. Besides, a limitation of our study is that we did not record the daily number of cigarettes smoked and the duration of smoking, which are important elements related to Hcy concentration [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations